Multistability and Complex Isotopy in Makam Music Analysis: The Link Between Cognition and Semiotics in Aesthetics of Turkish Music - Salvucci, Peter (Towarzystwo Naukowe KUL, 2024)
Multistability in perceptual psychology involves ambiguity or rivalry between two or more percepts of sensory stimuli. This phenomenon can be compared to the Greimassian concept of complex isotopy, where multiple terms of semantic content are simultaneously signified in the same reading of a text, providing multiple interpretational meanings. This study proposes that a key aesthetic principle of classical Turkish makam music involves the multistable perception of musical events, which in the semantic sense manifest as interoceptive, complex isotopies. The aesthetic of multiple subjective interpretations is examined in related traditional arts such as miniature art, poetry and theater. Generative theory is employed for compositional analysis in this study, as it reflects the cognitive apprehension of music. The principles of multistable perception as complex isotopy therefore provide a cognitive and aesthetic context to the author’s thesis proposal for a generative theory of makam music.